Fatores de risco para cicatriz renal após a primeira infeção febril do trato urinário - Freitas, Ana Cristina (2016)
Introduction: The urinary tract infection (UTI) is one of the most common paediatric infectious diseases and it increases the risk for hypertension and end-stage renal disease. Authors’ aim was to identify risk factors for permanent renal injury after a first febrile urinary tract infection. Methods: Retrospective analysis of clinical, laboratorial and imaging data of children aged 1 to 36 months hospitalized between January 2010 and December 2012 with the first febrile UTI, comparing with late renal scintigraphy results. Results: Seventy seven children were included - 53% female, median age of 5 months, Escherichia coli identified in 95%. Renal scintigraphy, performed after the acute episode, revealed renal scars in 19.5%. Cystourethrography was done in 21 patients and vesicoureteral reflux identified in 3. There was no statistically difference between children with and without renal scarring regarding gender, age, body temperature, C-reactive protein, plasmatic creatinine level, bacteriuria or urine nitrite test, urine bacteria identified, presence of vesicoureteral reflux or recurrence rate of UTI. Conclusions: The authors did not detect any clinical, laboratory or imaging data that may predict progression to renal scarring following a first episode of febrile UTI in children between 1 and 36 months.